2017
DOI: 10.1002/aic.15633
|View full text |Cite
|
Sign up to set email alerts
|

Removal of NO from flue gas using UV/S2 process in a novel photochemical impinging stream reactor

Abstract: A novel photochemical impinging stream reactor was developed for the first time. Removal process of NO from flue gas using sulfate radical ( ·) and hydroxyl radical (·OH) from UV‐light activation of persulfate (UV/S2 advanced oxidation process) was investigated in the novel reactor. Experiments were conducted to evaluate the effects of S2 concentration, solution pH, UV power, solution temperature, liquid‐gas ratio, flue gas flow, NO, SO2,and O2 concentrations on removal of NO. Mechanism and kinetics of NO re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Available NO abatement technologies can be divided into dry method and wet method. The wet method NO abatement technologies mainly include oxidation absorption, complex absorption, reducing absorption, etc. The dry method NO abatement technologies mainly include O 3 oxidation, catalytic oxidation, photocatalytic removal, selective catalytic reduction (SCR), selective noncatalytic reduction (SNCR), plasma removal, etc. These dry method removal technologies show good prospects in laboratory or pilot stage, but they also encounter several drawbacks, such as high costs, poor removal efficiency, high temperatures, or post-processing costs with associated secondary pollution problems. , Therefore, it is very necessary to further develop more economically effective NO-removing technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available NO abatement technologies can be divided into dry method and wet method. The wet method NO abatement technologies mainly include oxidation absorption, complex absorption, reducing absorption, etc. The dry method NO abatement technologies mainly include O 3 oxidation, catalytic oxidation, photocatalytic removal, selective catalytic reduction (SCR), selective noncatalytic reduction (SNCR), plasma removal, etc. These dry method removal technologies show good prospects in laboratory or pilot stage, but they also encounter several drawbacks, such as high costs, poor removal efficiency, high temperatures, or post-processing costs with associated secondary pollution problems. , Therefore, it is very necessary to further develop more economically effective NO-removing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of having strong oxidizing capacity and environmentally friendly process, ultraviolet light (UV)/peroxides (e.g., hydrogen peroxide, persulfate, and Oxone) advanced oxidation technologies recently have gained very widespread attention in the area of wastewater treatment and flue gas purification. ,,,,, In the previous works, ,,,, the authors and the other researchers investigated the removal of NO, SO 2 , and Hg 0 from simulated flue gas using UV/H 2 O 2 , UV/persulfate, and UV/Fenton­(-like) advanced oxidation technologies. The results show that UV/H 2 O 2 , UV/persulfate, and UV/Fenton­(-like) advanced oxidation technologies can efficiently remove NO, SO 2 , and Hg 0 from simulated flue gas, and the removal products can be recycled, which shows good prospects. ,,,, Nevertheless, the high prices of peroxides hinder further commercial applications of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant results ,, have shown that ultraviolet (UV)-light can effectively decompose PS and PMS to generate SO 4 • – radicals (see Table ). Photochemical SO 4 • – -based AOTs have received extensive attention in pollution control field owing to simple and green process, high reagent utilization, and free radical yield. ,, Liu et al proposed a NO removal process using UV (254 nm)/PS AOT in an UV-impinging stream reactor with vertical lamp tubes, and studied the performance, mechanism and mass transfer-reaction kinetics of NO removal using this technology. Their results indicated that the removal efficiency of NO reached 90.6%, and SO 4 • – and •OH were confirmed as the major active species for NO removal.…”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%
“…Thus, it has low operating cost due to low or no energy consumption. However, existing results based on the measurements of free radical yield by ESR technique ,,,,,,,,,,,,,,, showed that thermally activated SO 4 • – -based AOTs often had low yield of free radicals compared with other activation technologies such as photochemical, electrochemical, microwave activation, etc. Besides, high activation temperature will result in high self-decomposition rate of reagent and reduce the solubility of gaseous pollutants in solution (they correspond to high reagent consumption cost and large gas–liquid mass transfer resistance, respectively).…”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%
“…Aiming to integrate with the wet desulphurization process in order to simultaneously remove SO x , NO x , and PMs, various wet De-NO x methods have been researched extensively during the past decades [10,11]. Generally, NO accounts for more than 95% of NO x in diesel exhaust gas, but its solubility is very low [12,13]. erefore, one of the key points for wet De-NO x methods is to intensify mass transfer reactions at the liquid-gas interface.…”
Section: Introductionmentioning
confidence: 99%